Computer design of a thermoelectric generator for heat and electricity supply to heavy-duty vehicles - Anatychuk, L.I.; Lysko, V.V. (Journal of Thermoelectricity, 2021)
The physical model of the thermoelectric generator for the autonomous system of pre-heating of high-power vehicles is considered. The design of heat exchangers of heat supply and exhaust systems, which allow to ensure the optimal mode of operation of thermoelectric modules, has been determined by computer design. The design of a thermoelectric generator with an electric power of up to 350 W has been developed, which will be enough to supply electric energy to preheaters with a thermal power of 25-30 kW. Such a system, taking into account the thermal energy of the thermoelectric generator, will be equivalent to more powerful preheaters (36 - 40 kW), but will not require the use of battery electricity. Bibl. 8, Fig. 9, Table. 1.